Fiscal divergence and monetary integration in West Africa: What to draw from Darvas et al. (2005)? - Léleng Kebalo (Kiel Institute for the World Economy (IfW), 2019)
Fiscally undisciplined and divergent, West African countries are in transition for establishing a monetary union that must be effective by 2020 with the introduction of a single currency named "ECO". From the economic literature, it is argued that business cycles desynchronization is counterproductive to the viability of a monetary union. In addition, in the famous paper of Darvas et al. (Fiscal divergence and business cycle synchronization: irresponsibility is idiosyncratic, 2015), it is argued that the existence of fiscal divergences among countries despite the definition of fiscal convergence criteria is counterproductive to business cycles coherence. Using a gravity model based on 2SLS strategy, the author tests this theory by analyzing the effect of the fiscal divergences among the West African countries on their business cycles synchronization. To obtain robust results, the author uses two different business cycle series. The results underscore that a 1% increase in fiscal divergence is associated on average with reduced business cycle coherence by 0.105%, or a 1% decrease in fiscal divergence is associated on average with a better coherence of the business cycle by 0.105%. Because of the existing fiscal divergences among the West African area, this paper proposes some indirect and direct fiscal mechanisms need to significantly reduce them. Indeed, these fiscal divergences could be harmful to the viability of the future regional monetary union.
http://dx.doi.org/10.7910/DVN/FXL3OZ
Keywords: H61; H62; O47; 330; fiscal divergence; business cycles; regional integration; single currency; West Africa